Early Maize (Zea mays) in the North American Central Plains: The Microbotanical Evidence. Issue 2 (April 2022) - Adair, Mary J.; Duncan, Neil A.; Young, Danielle N.; Bozarth, Steven R.; Lusteck, Robert K.
Abstract : Artifacts, including ceramics, ground stone, and soil samples, as well as dental calculus, recovered from sites in the eastern North American central Plains were submitted to multiple laboratories for analysis of microbotanical remains. Direct accelerator mass spectrometer (AMS) dates of 361–197 cal BC provide evidence for the earliest use of maize ( Zea mays ssp. mays ) in this region. Squash ( Cucurbita sp.), wild rice (cf. Zizania spp.), and palm (Arecaceae sp.) microremains were also found. This research adds to the growing evidence of the importance of microbotanical analysis in documenting plant use and in the identification of early maize. The combined data on early maize from the eastern Plains adds to our understanding of the timing and dispersal of this crop out of the American Southwest. Alternative explanations for the adoption and early use of maize by eastern central Plains communities include its value as a secondary resource, as an addition to an existing farming strategy, or as a component of Middle Woodland rituals.